PRACTICES OF ENGLISH LANGUAGE TEACHERS IN ASSESSING JUNIOR HIGH SCHOOL STUDENTS’ WRITING PERFORMANCE - Tabernero, Karl Angelo (International Journal of Language and Literary Studies, 2024)
As English language teachers explore existing writing assessment approaches and strategies, it is, however, inevitable to encounter challenges in the different phases of writing assessment. The challenge is not confined alone to the development of writing assessment tools but more so to the establishment of fair and reliable results for writing performance. It has been argued that the gap between norms and traditions among language schools is one root of such a challenge. One writing assessment practice may work for one setting but not another. Therefore, the present study is intended to discover the writing assessment approaches and strategies employed by junior high school English language teachers in the context and to identify the relevant challenges they encountered in utilizing such writing assessment practices. To meet the research objective, a qualitative investigation through a narrative inquiry approach was employed. The data were gathered from seven (7) English language teachers in a junior high school in Bataan, Philippines. Self-made, semi-structured interview guides were utilized. The shared narratives from the interviews served as data subjected to thematic analysis. The research investigation revealed that English language teachers generally utilize scoring rubrics and an analytical approach to assess junior high school students’ writing performance. As a result, they have found challenges in assessing writing performance due to strict adherence to the components of scoring rubrics, time constraints, and the poor writing competencies of students. To address the issues, the study suggests writing assessment programs and training that promote contextualization, ICT integration, and learning autonomy. English language teachers value the importance of systematic writing assessment practices while also recognizing the roles of emerging practices that will establish not only fairness but also effectiveness that is responsive to the development of the English writing competencies of the students.